Analisis Faktor-Faktor Produksi Yang Mempengaruhi Produksi Kacang Panjang - Dionisius Jokong; I Made Budiasa; Ni Putu Sukanteri; Ni Putu Anglila Amaral (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Government support for increased vegetable consumption continues to be done by limiting the import of fruit and vegetable products. One type of vegetable that is widely consumed is long beans. The purpose of this study was to analyze the factors of production that affect the production of long bean farming and analyze the income of long bean farming. This research was conducted in Banjar Demulih, Demulih Village, Susut Subdistrict, Bangli Regency. The location of the study was determined intentionally (purposive sampling), and carried out from April to May 2021, the sample in this study was determined by census method, where the entire population was made respondents numbering 30 long bean farmers. The data analysis methods used in the study included an analysis of cobb-douglas production function estimates and cost and revenue analysis. Independent and dependent variable data includes long bean product (Y), land area (X1), Seed (X2), urea fertilizer (X3), NPK fertilizer (X4), Gandazil fertilizer (X5), pesticide (X6), and labor (X7). The results found that two (2) factors of production, namely land area and seeds, had a noticeable influence on long bean production, while the other five (5) factors had no real effect. The average profit of long bean farming in Banjar Demulih, Demulih village of Susut district of Bangli regency amounted to Rp 7,709,565 per 11.3 are per growing season, which is equivalent to Rp. 2,569,855 per 11.3 are per month. This profit is higher than bangli regency UMR which is Rp. 2,494,810 per month